Manajemen Anestesi pada Lansia dengan Peritonitis Sekunder: Sebuah Laporan Kasus: Indonesia - Enggar B, Dimas Fikri; Habibi, Bahtiar Yusuf; Maulana, Dendy (CV. Jasa Sukses Abadi, 2024)
Peritonitis is inflammation of the peritoneum, which is the thin serous membrane that covers the abdominal cavity and the organs inside. The incidence of peritonitis is more common in men than women with a prevalence of 68.4% in men. The largest age group is 10-19 years old, followed by 56-70 years old. Peritonitis is an acute abdomen which is an emergency. Delay in surgical procedures can cause severe organ dysfunction and worsen the prognosis of peritonitis. The type of surgical procedure performed to treat peritonitis is laparotomy. Laparotomy is performed through an incision in the abdominal wall down to the abdominal cavity. In laparotomy surgery, the type of anesthesia used is general anesthesia. General anesthesia is a temporary state of unconsciousness followed by the loss of pain throughout the body due to the administration of anesthetic drugs. Elderly patients generally have several anatomical and physiological changes associated with the aging process. A high risk of death is found in patients over 60 years of age due to concurrent pathological processes and comorbid factors. Although age is not a contraindication to anesthesia and surgery, the rate of death and perioperative illness in elderly patients is relatively higher. This case report discusses a 66 year old man with secondary peritonitis who complained of continuous abdominal pain for 3 days. An exploratory laparotomy was performed under general anesthesia on the patient. Careful planning and proper implementation during pre-operative, perioperative, and post-operative periods are essential for patient safety.